The Influence of the Bologna Process on Higher Education of the Republic of Moldova: Array - Mandaji, Elena (Journal of Danubian Studies and Research, 2020)
The higher education system in the Republic of Moldova has undergone a far-reaching transformation since the collapse of the Soviet Union in 1991. The higher education system, at the present time is in a state of active reforms, a turning point, which is, the country's joining of the Bologna process. The provisions of the Bologna process have become priority areas in the development of the country. Moldova today must build its system of quality education in accordance with the requirements of the European Union. It could be simply copy, but it is necessary to take into account the historical features of the education system development in Moldova and its current preferences. This article analyses some of the main achievements, challenges and influence of the Bologna Process on the higher education reform.